The role of affective commitment: Do servant leadership and non-physical work environment promote employee performance? - Ginting, Josafat Gracia; Sopiah, Sopiah; Suharsono, Naswan (Jurnal Fokus Manajemen Bisnis, 2024)
Maintaining the performance of a quality employee is the biggest challenge of the 4-star hotel industry in Malang City. The pandemic has caused hotels to experience a crisis due to a massive decline in occupancy. The economic crisis has made hotel management pay less attention to employee welfare during a hotel's recovery period. Employee welfare is a trigger for the expected performance instability. This study adopts an explanatory method with a quantitative approach. The study includes 242 participants employed in three 4-star hotels in Malang City. A sample of 151 respondents is chosen through stratified random sampling. Path analysis is used for data analysis. The results indicate that affective commitment, non-physical work environments, and servant leadership substantially impact employee performance. The association between employee performance and servant leadership may be partly influenced by affective commitment. However, affective commitment does not mediate the relationship between worker performance and the non-physical work environment.